The strange case of Dr. Jekyll and Mr. Hyde - Stevenson, Robert Louis 1850-1894; Olmstead, Kathleen (New York : Sterling Publications, 2006)
The Strange Case of Dr Jekyll and Mr Hyde is Robert Louis Stevenson's thriller allegory of a medical experiment gone wrong and dual personalities, one the essence of good, the other the essence of evil, fighting for supremacy in one man. Filled with suspense the book has had such an impact in popular culture that the expression "Jekyll and Hyde" has itself become synonymous with extremes of or inconsistent behavior.
Primary
Keywords: Physicians -- Juvenile fiction; Multiple personality; Self-experimentation in medicine; Paranormal fiction; Murderers -- Juvenile fiction; Horror tales; Good and evil; England -- London -- Juvenile fiction